An Investigation of Magnetic Field Influence in Underground High Voltage Cable Shields - Duc, H. B.; Minh, T. P.; Minh, D. B.; Hoai, N. P.; Quoc, V. D. (Engineering, Technology & Applied Science Research, 2022)
Magnetic fields and the shielding efficiency of the shields of underground high voltage cables are studied in this paper regarding several shielding configurations and materials. Shielding efficiency and magnetic fields are computed for shields with the same mesh but from different shielding materials, such as aluminum, ferrite, metal, and steel. In order to get the best shield configuration depending on the source characteristics and the material, a conducting ferromagnetic region with various thickness values is considered as shielding. A finite element model is introduced to investigate the influence of the parameters of magnetic fields and the shielding efficiency of underground high voltage cables. Furthermore, the reduction of the magnetic fields with or without shieldings is also presented. The developed method is performed with the magnetic vector potential formulations and validated on a practical problem.